Melatonin Mitigates Sarcopenic Obesity via Microbiota and Short‐Chain Fatty Acids: Evidence From Epidemiologic and In Vivo Studies - Xiaoxing Mo; Lihui Shen; Xinyu Wang; Wenqing Ni; Linyan Li; Lili Xia; Hongjie Liu; Ruijie Cheng; Lin Wen; Jian Xu; Liegang Liu (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Introduction Gut dysbiosis is closely related to the development of sarcopenic obesity (SO). Melatonin (MLT) regulates gut microbiota and promotes the production of short‐chain fatty acids (SCFAs). However, whether MLT affects SO through the gut microbiota and SCFAs remains unclear. This study aimed to investigate the effect and mechanism of MLT in SO induced by a high‐fat diet (HFD). Methods First, a case‐control study was conducted to explore the potential association between serum MLT levels and SO‐related parameters in 31 patients. Next, rats fed with a HFD were orally administered with MLT for 16 weeks, and obesity‐related metabolic disorders and muscle atrophy were measured. 16S rRNA gene sequencing and gas chromatography–mass spectrometry were used to detect gut microbiota and SCFAs, respectively. Gut barrier integrity was assessed by the expression of the Muc‐2 protein and tight junction proteins. Finally, faecal microbiota transplantation and SCFAs administration were performed to confirm the causal role of the gut microbiota and SCFAs in the effect of MLT on SO. Results The serum levels of MLT decreased in patients with SO (29.87 ± 6.71 vs. 24.94 ± 5.68, p < 0.01) and were closely associated with appendicular skeletal muscle mass index (r = 0.3514, p < 0.01) and handgrip strength (r = 0.2824, p < 0.05). MLT ameliorated obesity‐related metabolic disorders (p < 0.05), poor muscle mass (p < 0.05), strength (p < 0.05) and function (p < 0.05) and muscle atrophy (p < 0.05) in HFD‐fed rats. MLT regulated HFD‐induced gut dysbiosis, which was mainly characterized by increases in SCFAs‐related bacteria and SCFAs (p < 0.05). MLT recovered HFD‐induced impairment of gut barrier integrity by promoting the expression levels of Muc‐2, claudin‐1, occludin and zonula occluden‐1 proteins in the colon (p < 0.05). Correlation analysis showed that SCFAs‐related bacteria and SCFAs were negatively associated with SO. Faecal suspension from MLT‐treated rats promoted the production of SCFAs in recipient rats (p < 0.05). In addition, faecal suspension from MLT‐treated rats partially mitigated metabolic disorders (p < 0.05), poor muscle mass and function (p < 0.05) and muscle atrophy (p < 0.05) in recipient rats. SCFAs treatment alleviated the development of SO in HFD‐fed rats by suppressing metabolic disorders (p < 0.05), reducing muscle oxidative stress and inflammation (p < 0.05) and promoting protein synthesis through the AKT/mTOR/p70S6k signalling pathway (p < 0.05). Conclusions MLT mitigated HFD‐induced SO by regulating the gut microbiota and promoting the production of SCFAs. MLT might be a novel strategy for delaying the progression of SO.